PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN MEDIA PPT TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATERI LARUTAN ELEKTROLT DAN NON ELEKTROLIT KELAS X MIA 1 SMA N 13 BURU - Thalib, Alwia Bin; Mariwy, Abraham; Karepesina, Nur G (Molluca Journal of Chemistry Education (MJoCE), 2023)
ABSTRACT This research was conducted to find out the learning outcomes and learning outcomes of class X mia SMA 13 BURU in electrolyte and non-electrolyte solutions using the Guided Inquiry learning model. The sample of this research was students of class X mia, totaling 19 students. This research is descriptive quantitative with data collection techniques in the form of tests and observations, the instruments used are initial tests, worksheets, final tests and non-tests in the form of affective and psychomotor observation sheets. The results showed that in the initial test all students had not reached the KKM, and student learning outcomes in the form of the final test showed that 8 students (42%) is in the high category, 7 students (36%) were in good qualifications and 4 students (22%) are in sufficient qualification. Then the results of the N-gain analysis showed that 12 students (63%) were in the high category and 7 students (37%) were in the medium category and no students were in the low category. Thus the application of the Guided Inquiry Learning Model can improve the learning outcomes of class X mia students in electrolyte and non-electrolyte solutions at SMA 13 Buru .